Teaching natural and applied sciences in the Arabic language in schools and universities in the Kingdom of Saudi Arabia - Alowaydhi, Wafaa Hafize; al-Sayari, Faziah Ali Salem (Journal of Educational and Psychological Sciences, 2020)
The study aimed to know the percentage of supporters for the issue of teaching scientific and applied materials in the Arabic language and to reveal the reasons for support for this issue from the viewpoint of supporters, and to know the percentage of opponents and reveal the causes of opposition from the viewpoint of opponents, and the study sample consisted of (1223) individuals that included students from both phases Secondary and university students, science teachers, supervisors, science university professors The researchers followed the descriptive survey method using a questionnaire tool to survey the opinions of the sample on the issue, and the most prominent results are that 81.3% agree to teach natural and applied sciences subjects in the Arabic language instead of teaching them in other languages, and 18.7% see that they do not agree to teach science in the Arabic language, and that 91.1% Among the sample members who believe that understanding the science needs the student to be familiar with the language in which he is studying, if the mother tongue would be easier for him to understand the scientific subjects, while 8.9% do not agree to this, The results showed that 17.9% of respondents believed that teaching natural sciences in the Arabic language would be a reason for isolation from the world, while 82.1% saw the opposite. The study recommended a review of the teaching of natural and applied sciences in the Arabic language and a decision to use them in teaching natural and applied sciences because it is the mother tongue and to strengthen pride in them in the hearts of future generations.